MODELING, USING REGRESSION ANALYSIS, HEART RATE VARIABILITY DEPENDING ON THE CHARACTERISTICS ANTHROPO-SOMATIC INDICES IN HEALTHY GIRLS WITH HYPERKINETIC TYPE OF HEMODYNAMICS - Serheta, I.V.; Kovalchuk, V.V.; Dmytrenko, S.V.; Semenenko, A.I.; Ocheretna, O.L.; Perebetiuk, L.S.; Prokopenko, S.V. (World of Medicine and Biology, 2018)
In practically healthy girls of Podillia with a hyperkinetic hemodynamic type, using regression analysis, all 17 individual models of heart rate variability (HRV) parameters were constructed depending on the peculiarities of the constitutional parameters of body, age and brush compression forces with determination coefficients R2 greater than 0.7 (the determination coefficient R2 determines the admissible dependent variable in the group of statistical indicators of HRV from 81.0% to 95.7%; in the group of parameters of variation pulsometry - from 79.5% to 91.7%; in the indicator group vegetative homeostasis by Baevsky method - from 76.6% to 89.8%; in group of the spectral index of HRV - from 79.5% to 86.2%). The most commonly models of HRV included the width of distal epiphyses of long tubular limb bones (23.5%, mostly lower limb), brushing force (17.6%, uniformly on both hands), circumferential body dimensions (12.2%, predominantly by the expense of limbs) and age (11.8%).